Comparing success rates in central venous catheter salvage for catheter-related bloodstream infections in adult patients on home parenteral nutrition: a systematic review and meta-analysis. Issue 3 (26th May 2021) - Gompelman, Michelle; Paus, Carmen; Bond, Ashley; Akkermans, Reinier P; Bleeker-Rovers, Chantal P; Lal, Simon; Wanten, Geert J A
ABSTRACT: Background: Catheter-related bloodstream infection (CRBSI) is a life-threatening complication of parenteral nutrition. Therefore, optimal management, ideally with catheter salvage, is required to maintain long-term venous access. Objectives: We aimed to evaluate successful catheter salvage rates in patients on home parenteral nutrition (HPN). Methods: Studies were retrieved from medical databases, conference proceedings, and article reference lists. Data were collected relating to clinical outcomes of 3 treatments: systemic antibiotics, antimicrobial lock therapy (ALT), and catheter exchange. ORs and 95% CIs were calculated from a mixed logistic effects model. Results: From 10, 036 identified publications, 28 met the inclusion criteria (22 cohort studies, 5 case-control studies, and 1 randomized clinical trial), resulting in a total of 4911 CRBSIs. To achieve successful catheter salvage, the addition of an antimicrobial lock solution was superior to systemic antibiotics alone (OR: 1.75; 95% CI: 1.21, 2.53; P = 0.003). Recurrence of infection was less common in studies that used ALT than in those that used systemic antibiotics alone (OR: 0.26; 95% CI: 0.11, 0.61; P = 0.002). The catheter exchange group was excluded from multilevel regression analysis because only 1 included study applied this treatment. Successful salvage rates were highest for coagulase-negative staphylococci, followed by Gram-negative rods and Staphylococcus aureus . Conclusions: The addition of an antimicrobial lock solution seems beneficial for successful catheter salvage in HPN-dependent patients with a CRBSI. Future prospective randomized studies should identify the most effective and pathogen-specific strategy. This review was registered at www.crd.york.ac.uk/PROSPERO as CRD42018102959.